PERBANDINGAN HIDROLISIS GULA AREN DAN GULA PASIR DENGAN KATALIS MATRIKS POLISTIRENA TERIKAT SILANG (CROSSLINK) - DEDY ANWAR (JURNAL ILMIAH KOHESI, 2019)
Sugar is a carbohydrate that is used as a sweetener in food and drinks. In this study, palm sugar and white sugar were used. Palm sugar is a sugar in the form of brownish crystals, while white sugar is a crystal-shaped sugar white to yellowish white. The purpose of this study was to study the effect of white sugar (sucrose) with palm sugar on the product produced in a fixed bed catalytic reactor. The methodology used in this study is hydrolysis of sucrose to reducing sugars by a continuous method using a fixed-bed reactor. This fixed bed reactor contains a cation resin with a crosslinked polystyrene matrix. The results of the analysis showed that the concentration of glucose products was mostly produced by palm sugar . The glucose concentration in palm sugar 20 g/L and 30 g/L was 3.9852 g/L and 5.1691 g/L, while the glucose concentration in white sugar 20 g/L and 30 g/L was 3.7205 g/L and 4.9485 g/L.